A diamidinatogermylene as a Z-type ligand in a nickel(0) complex. Issue 40 (2nd October 2019) - Feng, Zhongtao; Jiang, Yixiao; Ruan, Huapeng; Zhao, Yue; Tan, Gengwen; Zhang, Li; Wang, Xinping
Abstract : We herein report the first example of germylene complexes in which the diaminogermylene acts as a Z-type ligand. Abstract : The reaction of the phosphine functionalized chlorogermylene 1 with Ni(COD)2 (COD = 1, 5-cyclooctadiene) afforded the bis-chlorogermylene ligated nickel(0) complex 2 in high yield. The dechlorination reaction of 2 with elemental potassium serendipitously yielded the diamidinatogermylene nickel(0) complex 3 . Single-crystal X-ray diffraction analysis reveals that the germanium center in 3 features a pyramidalized geometry, suggesting the germylene moiety in 3 acts as a Z-type ligand, which is further supported by theoretical calculations. Complex 3 represents the first example bearing a Z-type diaminogermylene ligand.